2017
DOI: 10.1177/0022219417704169
|View full text |Cite
|
Sign up to set email alerts
|

Reading Disability Spectrum: Early and Late Recognition, Subthreshold, and Full Comorbidity

Abstract: Several studies have reported high comorbidity for reading disability (RD) and psychiatric disorders. The aim of this study was to investigate the comorbidity of subthreshold and full psychiatric disorders with RD while comparing subgroups based on age of RD recognition (early vs. late). We analyzed data from 130 children with RD and 82 typically developing children aged 7 to 18 years. RD was assessed with the Dyslexia Differential Diagnosis Maastricht-Hungarian Standard Test. Psychiatric diagnoses were based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…The recruited studies found that psychiatric disorders are prevalent among children with SLD. This was obvious in 3 studies [2,20,21] which compared children with SLD to a control group of children with typical school performance. Table 2 shows that among the psychiatric comorbidity with SLD, ADHD came to the first position followed respectively by anxiety disorders and depression.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The recruited studies found that psychiatric disorders are prevalent among children with SLD. This was obvious in 3 studies [2,20,21] which compared children with SLD to a control group of children with typical school performance. Table 2 shows that among the psychiatric comorbidity with SLD, ADHD came to the first position followed respectively by anxiety disorders and depression.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Moreover, by further analysis of the prevalence rate of the subtypes of the anxiety disorders among 2 of the recruited studies [19,21], it was found that the most prevalent anxiety subtype with SLD was the specific phobia (specifically school phobia) as in Altay and Görker [19], followed by a separation anxiety disorder in Törő et al [21], and the generalized anxiety disorder was the least prevalent. This indicates that anxiety disorder in those children either school phobia or separation anxiety was the primary disorder.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations